2014
DOI: 10.1007/s00784-014-1206-5
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron light-based μCT to analyse the presence of dentinal microcracks post-rotary and reciprocating NiTi instrumentation

Abstract: Dentinal damage may occur following rotary and reciprocating instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 25 publications
1
42
0
2
Order By: Relevance
“…Pop et al 39) 2014 synchrotron radiation-based μCT (SRCT) analysis A significant increase in the number and length of microcracks was detected post-shaping. No significant difference between rotary and reciprocating instrumentation was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pop et al 39) 2014 synchrotron radiation-based μCT (SRCT) analysis A significant increase in the number and length of microcracks was detected post-shaping. No significant difference between rotary and reciprocating instrumentation was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies relating to dentinal cracks formation during root canal enlargement with rotary files (multifile systems) and reciprocating files (single-file systems) were rejected for our meta-analysis, as they did not meet the inclusion criteria. However, we also completed a basic review of these studies 20,[30][31][32][33][34][35][36][37][38][39][40] . We found that most of the results [30][31][32][33]36) were aligned with the results of our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture (9,12,13,32,34,40,63,65) or Complete Crack (23) or Vertical Root Fracture (VRF) (24) A line extending from the root canal space all the way to the outer surface of the root.…”
Section: Nomenclature Definitionmentioning
confidence: 99%
“…So far, only a few studies have explored the influence of files on the root canal walls with μCT . De‐Deus et al concluded that root canal instrumentation with WaveOne, BioRace, Reciproc , ProTaper Next, and Twisted Files Adaptive did not result in more microcracks than before the instrumentation.…”
Section: Micro‐computed Tomography (μCt) Studiesmentioning
confidence: 99%
“…). Pop et al concluded that although some unprepared teeth from the control group presented dentinal microcracks even before instrumentation, their number and length increased after instrumentation with ProTaper and WaveOne files.…”
Section: Micro‐computed Tomography (μCt) Studiesmentioning
confidence: 99%